Anxiety in Pregnant Women During the Covid-19 Pandemic: A Systematic Review with Meta-Analysis - Pitaloka, Cyntia Puspa; Tjokroprawiro, Brahmana Askandar; Sulistyowati, Muji (Indonesian Socety of Obstetrics and Gynecology, 2024)
Objective : This study systematically reviewed and meta-analysis the prevalence and factors associated with anxiety in pregnant women during the pandemic. Methods : We searched PubMed MEDLINE, Web of Science, Scopus, ProQuest, EBSCO, Science Direct, and Garuda journal databases in July 2021 and updated them in October 2021. All English and Bahasa journal articles from December 2019 were included in the search. We included studies that investigate factors affecting anxiety exclusively in pregnant women. The primary outcome was the prevalence ratio. The secondary outcome was the risk and protective factors as the independent variable. Joanna Briggs Institute Critical Appraisal Tools and RevMan 5.4 were used to do the analysis. Results: After screening 2082 articles, we included 21 studies with 42.177 pregnant women. The pooled prevalence of anxiety was estimated at 28% (95% CI, 23-33.3). We found that 12 of the 21 studies contributed to 8 risks and 1 protective factor significantly in the meta-analysis. Not married/divorced/widowed, monthly income < 780 USD, screen time > 3 hours/day, history of exposure to COVID-19, complications in the current pregnancy, sleep less than 7 hours per day, subjective poor sleep quality, and high perception of vulnerability were risk factors. Meanwhile, the protective factor was trust in the government's official media. Conclusion : There is a significant increase in the prevalence of maternal anxiety during the pandemic. Mental health screening during the antenatal visit must be carried out, and interventions to lower the anxiety level must be planned to prevent further harm. Keywords: pregnancy, anxiety, mental health, COVID-19, pandemics Tujuan: Penelitian ini meninjau secara sistematis dan meta-analisis prevalensi dan faktor yang berhubungan dengan kecemasan pada ibu hamil selama pandemi. Metode: Pencarian dilakukan pada database jurnal PubMed MEDLINE, Web of Science, Scopus, ProQuest, EBSCO, Science Direct, dan Garuda pada Juli 2021 dan memperbaruinya pada Oktober 2021. Semua artikel jurnal berbahasa Inggris dan Indonesia dari Desember 2019 dimasukkan dalam pencarian. Kami menyertakan penelitian yang menyelidiki faktor-faktor yang mempengaruhi kecemasan secara eksklusif pada wanita hamil. Hasil utama adalah prevalensi. Hasil sekunder adalah faktor risiko dan protektif sebagai variabel independen. Joanna Briggs Institute (JBI) critical appraisal guideline digunakan untuk menilai kualitas penelitian yang disertakan. RevMan 5.4 dan Jamovi 2.0 digunakan untuk melakukan analisis kuantitatif Hasil : Setelah menyaring 2082 artikel, kami menyertakan 21 penelitian dengan 42.177 wanita hamil. Prevalensi kecemasan yang terkumpul diperkirakan sebesar 28% (95% CI, 23-33,3). Kami menemukan bahwa 12 dari 21 studi berkontribusi terhadap 8 risiko dan 1 faktor pelindung secara signifikan dalam meta-analisis. Faktor risiko yaitu kondisi tidak menikah/bercerai/janda, pendapatan bulanan < 780 USD, waktu layar > 3 jam/hari, riwayat paparan COVID-19, komplikasi pada kehamilan saat ini, tidur kurang dari 7 jam per hari, kualitas tidur subyektif buruk, dan tingginya persepsi kerentanan. Sedangkan faktor protektif adalah kepercayaan terhadap media resmi pemerintah. Kesimpulan : Terdapat peningkatan prevalensi kecemasan ibu yang signifikan selama pandemi. Skrining kesehatan mental selama kunjungan antenatal harus dilakukan, dan intervensi untuk menurunkan tingkat kecemasan harus direncanakan untuk mencegah bahaya lebih lanjut. Kata kunci: kehamilan, kecemasan, kesehatan mental, COVID-19, pandemi